ANALISIS ELASTISITAS PERMINTAAN TERHADAP PERUBAHAN HARGA SEPEDA MOTOR SCOOPY DI PT. ASTRA MOTOR SUMBAWA BESAR - Nia Kurniasih; I Nyoman Sutama; U Usman (Jurnal Ekonomi & Bisnis, 2023)
This study aims to analyze the level of demand elasticity regarding changes in the price of Honda Scoopy motorbikes at PT. Astra Motor Sumbawa Besar 2017-2021. Type of this study was a descriptive with a quantitative approach, namely the study that aims to describe the elasticity of demand for changes in the price of Honda Scoopy motorbikes at PT. Astra Motor Sumbawa Besar that occur as they are, supported by data in the form of numbers generated from actual conditions. In this study, the data used was obtained from sales reports documents for Honda Scoopy motorbikes at PT. Astra Motor Sumbawa Besar 2017-2021. The data collected was analyzed using the concept of elasticity of demand which was calculated based on the value of the demand elasticity coefficient to determine the impact of price increases on demand for Honda Scoopy motorbikes at PT. Astra Motor Sumbawa Besar 2017-2021. The results of this study showed that the level of elasticity of demand for Honda Scoopy motorbikes at PT. Astra Motor Sumbawa Besar 2017-2021 was in the elastic category. This can be known based on the value of the demand elasticity coefficient for Honda Scoopy motorbike at PT. Astra Motor Sumbawa Besar in 2017-2021 is greater than 1 (e > 1). This result means that every 1 percent change in price, it will cause a change in quantity demanded of more than 1 percent.